Population of the World and Regions as the Principal Energy Consumer - Lizunkov, Vladislav; Politsinskaya, Ekaterina; Malushko, Elena; Kindaev, Alexandr; Minin, Mikhail (International Journal of Energy Economics and Policy, 2018)
The article presents the forecast of consumption of the world energy volume taking into account the population growth up to 2030. While arranging the study it was found that most countries are in the process of rapid population growth, followed by a phase of outstripping growth in energy consumption and economics industrialization. The levels and dynamics of primary energy consumption per capita are fundamentally different in developed and developing countries. If developed countries have already passed the peak of their per capita energy consumption, then developing countries will witness the increase of per capita energy consumption. It has been established that a number of developing countries will not be able to significantly increase their per capita energy consumption during the forecast period with the outstripping population growth, and the problem of energy poverty will remain acute for them. Therefore the article substantiates the only theoretically possible way of overcoming the crisis which is represented by a large-scale use of renewable energy sources: solar, wind, oceanic which are considered to be non-conventional or alternative ways of obtaining energy. It is less dangerous, practical, durable and environmentally sound. Keywords: energetics, effective energy consumption, energy poverty, renewable energy sources JEL Classifications: C62, N70, O13, P48